Regulatory Changes and Role of Audit Committee : Indian Evidence - Heggede, Savitha; Jadhav, Aditya Mohan (Indian Journal of Finance, 2021)
Corporate governance reforms have emphasized on the need for an audit committee and expanded its role and responsibilities over the last two decades. The purpose of this study was to examine the evolution of audit committee and document changes in audit committee’s composition and responsibilities in the Indian context. This article investigated the impact of regulatory changes on audit committee composition in terms of size, independence, and meeting frequency from 2003 – 2018. This study found that the size of the audit committee and its meeting frequency has increased over the years. Our findings suggested that in the absence of mandatory compliance regarding independence of audit committee, we saw a considerable decline in fully independent audit committees. We also documented increased presence of executive directors on audit committee.